Soil bacterial community is influenced by long‐term integrated soil fertility management practices in a ferralsol in Western Kenya - Bolo, Peter; Mucheru-Muna, Monicah; Mwirichia, Romano K.; Kinyua, Michael; Ayaga, George; Kihara, Job Maguta (Wiley, 2024)
Introduction soil bacterial community structure, abundance and diversity, important in biogeochemical cycling, are influenced by several anthropogenic and edaphic factors. Numerous agronomic practices have been promoted to improve soil fertility and crop production in western Kenya, but little is known on their impacts on soil microbial diversity in the region. Materials and Methods In this study, conducted in 2019, we assessed the influence of various long‐term (17 years) agronomic management practices, involving application of farmyard manure (FYM) either sole or under different combinations with inorganic nitrogen (N), phosphorus (P) and potassium (K), using 12 treatments, on bacterial community composition, relative abundance and diversity. The bacterial community composition was assessed through amplicon sequencing on an Illumina Miseq platform conducted in MR DNA Laboratory, USA. Results The soil bacterial community composition and diversity were predominantly higher under management practices with application of FYM, either sole or in combination with inorganic fertilisers compared to treatments with either sole NPK fertiliser or no input application. Certain bacterial taxa, involving Proteobacteria, Bacteroidetes, Nitrospirae, Fusobacteria, Nitrospinae and Actinobacteria predominated in management practices where FYM was added either solely or in combination with chemical fertilisers. In addition, several soil chemical parameters showed significant influences on bacterial composition, relative abundance and diversity indices. Soil pH, soil organic carbon (SOC), N, K, Ca, Mg, Cu, Zn, Fe and cation exchange capacity consistently showed strong positive correlation with numerous bacterial phyla. Bacterial phyla were significantly affected by treatments. Some bacterial phyla, like Chloroflexi and Acidobacteria , were mostly dominant in treatments applied with organic inputs but were depressed under carbon‐deficient treatments (no‐input control and sole NPK application treatments). Conclusion This study revealed that long‐term agricultural management practices that seek to improve SOC content and nutrient availability also stimulated bacterial diversity and shifted bacterial composition.